2020
DOI: 10.3389/fphar.2020.566783
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera Lam and its Therapeutic Effects in Immune Disorders

Abstract: Moringa oleifera Lam., a plant native to tropical forests of India, is characterized by its versatile application as a food additive and supplement therapy. Accumulating evidence shows that Moringa plays a critical role in immune-related diseases. In this review, we cover the history, constituents, edibility, and general medicinal value of Moringa. The effects of Moringa in treating immune disorders are discussed in detail. Moringa can not only eliminate pathogens, including bacteria, fungi, viruses, and paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 66 publications
(80 reference statements)
0
40
0
Order By: Relevance
“…An increase in the expression of both VEGF and TGF-β1 genes showed the proliferative properties of M. oleifera extract that might have contributed to its wound-healing action. Apart from these cytokines, earlier studies report that Moringa affects the release of other cytokines involved in inflammation and immune reactions such as prostaglandins, cyclooxygenase, tumor necrosis factor (TNF-α), interferons (INF-β), immunoglobulins, and interleukins, to name a few [ 39 ]. Some of these cytokines might have also contributed to the proliferative changes observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the expression of both VEGF and TGF-β1 genes showed the proliferative properties of M. oleifera extract that might have contributed to its wound-healing action. Apart from these cytokines, earlier studies report that Moringa affects the release of other cytokines involved in inflammation and immune reactions such as prostaglandins, cyclooxygenase, tumor necrosis factor (TNF-α), interferons (INF-β), immunoglobulins, and interleukins, to name a few [ 39 ]. Some of these cytokines might have also contributed to the proliferative changes observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Calculating the ratio of Minimal Bactericidal Concentration (MBC)/Minimal Inhibition Concentration (MIC) showed that the extract of M. oleifera seeds was bactericidal against all susceptible bacterial species (MBC/MIC of between 1 and 2). This activity can be explained by the fact that the extract of M. oleifera seeds is high in natural compounds such as pterygospermin, benzyl isothiocyanate, and 4-(L-rhamnopyra nosyloxy) benzylglucosinolate, all of which have strong antibacterial activity [32], [33], [34].…”
Section: Potential Of Moringa Oleifera As Antibacterialmentioning
confidence: 99%
“…Flavonoids will inhibit the binding of ATPase and phospholipase enzymes so that the permeability of Gram negative Leaves cell membranes will be disturbed. Flavonoids will also form compounds with dissolved extracellular proteins, which will cause damage to the bacterial cell membrane so that the function of the cell membrane is inhibited and the intracellular compounds of the bacteria are released [32], [34].…”
Section: Potential Of Moringa Oleifera As Antibacterialmentioning
confidence: 99%
“…In addition to its active compounds with antimicrobial activities such as kaempferol and isoquercitrin, amino acids and peptides, and lectins in MO were thought to be the primary modulators of gut microbiomes composition ( Xiao et al, 2020 ). Crosstalk between protein/amino acid from diets may alter gut microbiomes’ profiles and functions, further impacting the host’s metabolism ( Zhao et al, 2019 ; Wu et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%